The influence of possession status on the physical output of male international hockey players. Issue 2 (April 2022) - Cunniffe, Eoin; Connor, Mark; Beato, Marco; Grainger, Adam; McConnell, Walter; McCarthy Persson, Ulrik; Delahunt, Eamonn; Boreham, Colin; Blake, Catherine
The aims of this investigation were to describe the physical output of hockey relative to possession status, and to identify differences in physical output during each possession category with respect of match result. Ten international matches were analysed utilizing Sportscode to identify in and not in possession instances. 24 players (age 26 ± 4) wore a 10 Hz GPS device to track physical output. Linear Mixed Models and post hoc pairwise comparisons were utilised to compare the physical output in each possession category within each position and relative to match result. Significant main effects were found for possession status on several physical output metrics (p ≤ 0.05). For all positions except forwards, not in possession instances were more physically demanding than in possession instances for metrics such as relative total distance, explosive distance, and high-speed running (>5.5 m.s −1 ). No significant difference was identified between possession category physical output aligned with match result (p > 0.05). This study shows for the first time that not in possession instances were more physically demanding than in possession instances for defenders, outside backs and midfielders. For not in possession instances, relative total distance and high-speed running was, on average, 13% and 41% higher compared to in possession instances. Furthermore, there was no statistical difference in physical output for any position during each possession category relative to the match result.